1999
DOI: 10.1074/jbc.274.15.10641
|View full text |Cite
|
Sign up to set email alerts
|

Functional Interactions of Transforming Growth Factor β-activated Kinase 1 with IκB Kinases to Stimulate NF-κB Activation

Abstract: Several mitogen-activated protein kinase kinase kinases play critical roles in nuclear factor-B (NF-B) activation. We recently reported that the overexpression of transforming growth factor-␤-activated kinase 1 (TAK1), a member of the mitogen-activated protein kinase kinase kinase family, together with its activator TAK1-binding protein 1 (TAB1) stimulates NF-B activation. Here we investigated the molecular mechanism of TAK1-induced NF-B activation. Dominant negative mutants of IB kinase (IKK) ␣ and IKK␤ inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
181
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(190 citation statements)
references
References 50 publications
(58 reference statements)
8
181
0
1
Order By: Relevance
“…It is possible that this inhibition is the result of inhibition of an upstream kinase. Recent studies have shown that TAK1 is a major kinase directly responsible for activation of IKK pathway (44,45). We also found that pinitol suppresses NF-nB-dependent reporter gene expression.…”
Section: Discussionsupporting
confidence: 53%
“…It is possible that this inhibition is the result of inhibition of an upstream kinase. Recent studies have shown that TAK1 is a major kinase directly responsible for activation of IKK pathway (44,45). We also found that pinitol suppresses NF-nB-dependent reporter gene expression.…”
Section: Discussionsupporting
confidence: 53%
“…17 MAP3K7 with its activator TAB1 (TAK1-binding protein 1) can activate NF-kB by an NIK (NF-kBinducing kinase)-independent mechanism, 18 but with a functional interaction with IKK (IkB kinase) a and IKKb. 19 This activation of NF-kB has been implicated in liver tumor formation. 20 However, several members of the IAP (inhibitors of apoptosis) family, such as XIAP, NAIP and ML-IAP, activate JNK1 survival pathway through interaction with MAP3K7 and its activator TAB1.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies, however, indicate that TAK1 plays a major role in TNF-␣-induced NF-B activation through its interaction with TAB1 and TAB2. For example, TAK1 can bind and activate IKK␤ leading to NF-B activation (74). TAK1 also has been shown to be recruited by the TNFR1 through TRADD, TRAF2, and RIP (21).…”
Section: Discussionmentioning
confidence: 99%